A Concept of the Russian Agro-Food Sector. Issue 5 (3rd June 2018) - Borodin, K.
Abstract : The instability of the Russian economy (because of its dependence on the international hydrocarbons market and the extension of the 2014 sanctions) raises the need for a comprehensive concept of the Russian agro-food sector. This concept should include a set of long-term priorities and objectives for developing the agro-food sector. This article examines the macroeconomic problems facing the Russian agro-food sector and considers several long-term objectives for fostering economic growth, including the promotion of small and medium businesses and the integration into new international markets. The Eurasian Economic Union forms a transportation corridor, directly linking western Europe with China, India, and central and Southeast Asia. Particular attention is given to the development of export infrastructure (port facilities, trans-shipment bases, etc.), the creation of common standards in the transportation sector, and the convergence of transportation and transit tariffs. It is argued that small and medium businesses are highly adaptable, with the capacity to quickly adopt new technologies, to respond to new investment and changing consumer demand, and to integrate into value chains connected to new markets.